P-39 Association between VO2peak and hospitalization: a 3-year follow-up study in 1308 cardiac outpatients. (18th November 2016) - Grazzi, G; Chiaranda, G; Myers, J; Codec, L; Pasanisi, G; Napoli, N; Guerzoni, F; Volpato, S; Conconi, F; Mandini, S; Mazzoni, G
Abstract : Background/Aim: Cardiovascular diseases (CVD) are the leading cause of mortality in the world and 'produce immense global health and economic burdens', mostly attributable to hospital costs.1 The determination of peak oxygen consumption (VO2peak) is used for assessing disease severity, predicting prognosis, and examining the effectiveness of training programs for individuals with CVD. 2 Aim of the study was to determine the association between VO2peak estimated by a moderate 1-km treadmill walk (1km-TWT)3 and all-cause hospitalization in cardiac outpatients. Methods: We studied 1308 men aged 25-85 years at baseline, referred to our Center for an exercise-based secondary prevention programme. Participants were instructed to select a walking pace at a perceived intensity of 11-13 on the 6-20 Borg Scale to be maintained during the 1-km-TWT. The equation for VO2peak estimation was applied considering age, BMI, heart rate, and time to complete the 1-km3. All-cause hospitalization was checked 3 years after enrollment. Results: Patients were subdivided into tertiles of VO2peak. Estimated VO2peak resulted 19.62.4, 23.81.1, and 29.03.0 mL/kg/min for the first (n=436, LOW FIT), second (n=436, MODERATE FIT), and third (n=436, HIGH FIT) tertile, respectively. During the following 3 years, hospitalizations were 203 for LOW FIT group (47% of the sample), 151 for MODERATE FIT group (35% of the sample), and 109 for HIGH FIT group (25% of the sample) (Figure). Compared to the LOW FIT group, the fully-adjusted hazard ratios for hospitalization were 0.79 (95%CI 0.59 to 1.05, P=0.10) for the MODERATE FIT group, and 0.53 (95%CI 0.35 to 0.79, P=0.002) for the HIGH FIT group (P for trend ≥0.0001). Hospital stay was 3654, 1963, and 1090 days for LOW, MODERATE, and HIGH FIT groups, respectively. The mean healthcare costs for hospitalization during the 3-years tracking period were 36% and 64% lower in the HIGH FIT and MODERATE FIT groups versus LOW FIT group (1.74, 1.11, and 0.63 million euros respectively). Conclusions: An inverse association was found between exercise capacity and all-cause hospitalization in stable outpatients with cardiovascular disease. The lower VO2peak was associated with higher rates of hospitalization, independently of traditional cardiovascular risk factors and disease severity. The higher the baseline VO2peak, the lower the hospitalization rate, the shorter the length of hospital stay, and the lower the corresponding healthcare costs. The 1km-TWT represents a simple tool for assessing cardiorespiratory fitness and for predicting prognosis in patients with CVD. References: Mozaffarian D, Benjamin EJ, Go AS, et al . Heart Disease and Stroke Statistics-2015 Update. A Report From the American Heart Association. Circulation 2015;131 :e29–e322. Arena R, Myers J, Williams A, et al . Assessment of functional capacity in clinical and research settings: a scientific statement from the American Heart Association Committee on Exercise, Rehabilitation, and Prevention of the Council on Clinical Cardiology and the Council on Cardiovascular Nursing. Circulation 2007;116 (3):329–43. Chiaranda G, Myers J, Mazzoni G, et al . Peak oxygen uptake prediction from a moderate, perceptually regulated, 1-km treadmill walk in Male cardiac patients. J Cardiopulm Rehabil Prev 2012;32 :262–9.